New Ternary Transition Metal Complexes of 2-{[(2-aminophenyl)imino] methyl}Phenol and Metformin: Synthesis, Characterization and Antimicrobial Activity - S. S. Sharma; J. V. Ramani; D. P. Dalwadi; J. J. Bhalodia; N. K. Patel; D. D. Patel; R. K. Patel (E-Journal of Chemistry)
Complexes of Co(II), Ni(II) and Cu(II) were synthesized from Schiff base 2-{[(2-aminophenyl)imino]methyl}phenol and metformin. The authenticity of the transition metal complexes were characterized by elemental analyses, conductance and magnetic susceptibility measurements, as well as spectroscopic (IR, electronic) and thermal studies. IR spectral studies revealed the existence of the ligands in the amine form in the solid state. The magnetic and electronic spectral studies suggest an octahedral geometry for all the complexes. The metformin acts as a bidentate ligand and Schiff base of o-phynelendiamine and salicylaldehyde acts as a tridentate ligand. Antimicrobial screening of the Schiff base, metformin and transition metal complexes were determined against the bacteria Escherichia coli and Bacillus megaterium.